Cu(i)–I coordination polymers as the possible substitutes of lanthanides as downshifters for increasing the conversion efficiency of solar cells. Issue 14 (12th March 2020) - López-Molina, Jesús; Hernández-Rodríguez, Cecilio; Guerrero-Lemus, Ricardo; Cantelar, Eugenio; Lifante, Ginés; Muñoz, Marta; Amo-Ochoa, Pilar
Abstract : From microns to nano Cu(i )–I composite films with higher external quantum efficiency as substitutes of lanthanides in solar cells. Abstract : This study tries to provide new solutions to increase the efficiency of conversion of photons in solar cells, using photoluminescent Cu(i ) coordination polymers (CPs) as possible alternative materials of lower cost, than those used today, based on lanthanides. The selected CP of chemical formula [Cu(NH2 MeIN)I] n (NH2 MeIN = methyl, 2-amino isonicotinate) absorbs in the utraviolet and emits in the visible region, being also easily nanoprocessable, by a simple and one-pot bottom-up approach. Nanofibers of this CP can be embedded in organic matrices such as ethyl vinyl acetate (EVA), forming transparent and homogenous films, with a thermal stability of up to approximately 150 °C. These new materials maintain the optical properties of the CP used as a dopant, ([Cu(NH2 MeIN)I] n ), with emission in yellow (570 nm) at 300 K, which is intensified when the working temperature is lowered. In addition, these materials can be prepared with varying thicknesses, from a few microns to a few hundred nanometers, depending on the deposition method used (drop casting or spin coating respectively). The study of their external quantum efficiency (EQE) found an increase in the UV range, which translates into an increase in the conversion efficiency. The optimal CP concentration is 5% by weight in order to not diminish the transparency of the composite material. The calculated cost on the possible incorporation of this material into solar cells shows a 50% decrease over the cost reported in similar studies based on the use of lanthanides.